Africa Agricultultural Adaptation Atlas - Rosenstock, Todd Stuart; Steward, Peter Richard; Youngberg, Brayden; Vyas, Shalika; Wood-sichra, Ulrike; Muller, Lolita; Thornton, Philip; Achicanoy-Estrella, Harold Armando; Chilambe, Pedro Anglaze; Ramirez-Villegas, Julian; Mehrabi, Zia; Ormaza Zulueta, Naia; et al. (European Organization for Nuclear Research, 2025)
The Africa Agriculture Adaptation Atlas is a aimed at strengthening adaptation programming across Africa using data driven decision-making. We aim to create scientifically robust data rich insights to inform decision-making and facilitate the development of effective adaptation programs, policies, and investments. These notebooks are the core of the Africa Agriculture Adaptation Atlas project and are designed to be user-friendly, scalable, and open. We adopt a story-based aproach to the notebooks with the aim of giving users direct and specific insights for their needs as quickly and easily as possible. This project is lead by the Alliance of Bioversity International and CIAT and is build in collaboration with a consortium of CGIAR centers, the Better Planet Laboratory at University of Colorado, Boulder and many other institutions, programs, and individuals.